Safagamyces marinus gen. et sp. nov. (Halosphaeriaceae, Sordariomycetes) from Red Sea mangroves, Egypt - Bakhit, Mahmoud S.; Abdel-Wahab, Mohamed A. (Phytotaxa, 2022)
Safagamyces marinus gen. et sp. nov. was recorded from decaying stem of Phragmites australis inside Safaga mangrove is described and illustrated in this article. Phylogenetic analyses of SSU and LSU rDNA sequences dataset placed the new fungus as a distinct branch basal to a node that contains the three asexual marine genera: Cirrenalia, Cucurbitinus and Pseudolignincola in the family Halosphaeriaceae. The fungus is characterized by straight or slightly curved, branched, smooth, 2-6 septate conidia and the sympodial conidial proliferation. Conidial cells increase in size and pigmentation from hyaline at the base to dark-brown at the apex. The new taxon is compared with other asexual fungi in Halosphaeriaceae.